Characterization of vacuum plasma spray NiCoCrAlY coating resistant to high temperature oxidation - Mihailo Mrdak; Časlav Lačnjevac; Marko Rakin; Nikola Bajić (Zaštita Materijala)
Protective vacuum plasma spray VPS - NiCoCrAlY coating is used on sections of gas turbines to allow for longer and more reliable operation of sections exposed to aggressive effects of high temperature oxidation. Depositing of NiCoCrAlY alloy powder was done with the vacuum plasma spray system of the Plasma Technik - AG Companyon the A-2000 control unit using the plasma F4 gun. To test the mechanical properties and microstructure of the NiCoCrAlY coating, the powder was deposited on Č.4171 (X15Cr13 EN10027) steel substrates.To examine the microstructure of the coating in the heat-treated state, the powder was deposited on an IN738LC alloy substrate, which was pre-heated to a temperature of 750 to 800°C before deposition of the powder. The coating with the IN738LC alloy substrate was heat-treated at 1150°C for 2 hours in anargon shielded atmosphere. Mechanical testing of the microhardness of the coating was done using the HV0.3 method and the tensile bond strength using the tension method. The morphology of the powder particles and the morphology of the surface of the deposited coating were examined using a scanning electron microscope (SEM). The microstructure of coating layers in deposited state was tested on an optical microscope (OM). After thermal treatment, etching of the coating was done in the reagent CuSO4 + HCl aqueous solution. Analysis of the microstructure of the coating after etching was performed on the SEM, on the basis of which a score of the quality of the diffusion VPS - NiCoCrAlY coating was given.